2021
DOI: 10.1108/idd-08-2020-0106
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding a football club’s social media network: an exploratory case study of Manchester United

Abstract: Purpose The purpose of this work is to study how different stakeholders of a football club engage with interactions online through Twitter. It analyses the football club’s Twitter network to discover influential actors and the topic of interest in their online communication. Design/methodology/approach The authors analysed the social networks derived from over two million tweets collected during football matches played by Manchester United. The authors applied social network analysis to discover influencers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…Our findings are also comparable to Chadwick et al (2021), who found that the Twitter account of a high impact brand (EPL) containing several distinct opinion leaders can lead to the development of a unique amplified network. Another relevant study by Guzmán et al (2021) examined tweets that were collected during Manchester United’s matchdays. The study used SNA to identify influential users within the network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are also comparable to Chadwick et al (2021), who found that the Twitter account of a high impact brand (EPL) containing several distinct opinion leaders can lead to the development of a unique amplified network. Another relevant study by Guzmán et al (2021) examined tweets that were collected during Manchester United’s matchdays. The study used SNA to identify influential users within the network.…”
Section: Discussionmentioning
confidence: 99%
“…Like a mega sporting event, where key social media influencer networks were identified to have consisted of journalists, fans and players, among other related stakeholders (Guzmán et al, 2021), the Squid Game social network showed organized participation of a professional and non-professional fan base, who acted as key influencers or opinion leaders. An in-depth analysis of opinion leader characteristics within the network highlights several citizens, film and TV influencers, and even Netflix’s own different territory accounts that were influential within the network.…”
Section: Discussionmentioning
confidence: 99%
“…Esta red social proporciona una rápida interacción entre los usuarios y contribuye fuertemente a la difusión de información a través de mecanismos virales. En el contexto de la comunicación deportiva, Twitter ayuda a hacerse una idea de los principales temas tratados por los usuarios (González et al, 2021;Huang, Shen & Li, 2018; Méndez-Guzmán, Zhang & Ahmed, 2021). La conversación abierta en Twitter permite explorar cómo se desarrolla la marca de los atletas durante un período de tiempo (Su, Baker, Doyle & Kunkel, 2020) y las diferentes formas en que los equipos pueden construir relaciones sólidas con sus aficionados (Naraine, 2019;Wang, 2021).…”
Section: Introductionunclassified
“…This social network provides quick interaction among users, and strongly contributes to the spread of information through viral mechanisms. In the context of sports communication, Twitter helps to get a picture of the main topics discussed by users (González et al, 2021;Guzmán et al, 2021;Huang et al, 2017). The open conversation in Twitter allows us to explore how athlete branding unfolds over a period of time (Su et al, 2020), and the different way teams can build strong relationships with fans (Naraine, 2019;Wang, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are already several research works on the ways in which large sport teams and mass sporting events (such as the Olympic games or world soccer championships) leverage social networks (Abeza et al, 2014;Clavio et al, 2013;Guzmán et al, 2021;Jensen et al, 2015;X. Wang, 2015;Yu & Wang, 2015), in the case of niche sports the research is much more limited (Mastromartino et al, 2020;Trivedi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%